The Effect of Adaptive Supervision, Employee Competence and Organizational Commitment on Employee Performance through Work Discipline as an Intervening Variable at the Binjai City Secretariat Office - Ghaly Abacha Ginting; Sri Rahayu; Mesra B (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to examine the influence of adaptive supervision, employee competence, and organizational commitment on employee performance with work discipline as an intervening variable at the Binjai City Regional Secretariat Office. The study used a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through the SmartPLS 3.0 application to analyze the data collected from the employees. The results of the measurement model evaluation showed that the entire construct met the criteria of convergent validity, discriminant validity, and reliability, as indicated by the values of outer loading, Average Variance Extracted (AVE), Composite Reliability, and Cronbach's Alpha which were above the required limits. The results of the structural model evaluation showed a strong clear power of the model, with an adjusted R-square value of 0.783 for work discipline and 0.842 for employee performance. The results of the hypothesis test revealed that organizational commitment has a positive and significant effect on work discipline and employee performance. In addition, work discipline has been shown to mediate the relationship between organizational commitment and employee performance. In contrast, adaptive supervision and employee competence do not show a significant direct or indirect influence on employee performance through work discipline. Work discipline also does not have a significant direct effect on employee performance. Overall, these findings show that organizational commitment is the most dominant factor in improving employee performance, so strengthening employee loyalty and attachment to the organization is an important aspect in encouraging sustainable performance improvement in the public sector.